2004
DOI: 10.1023/b:jice.0000026916.15278.2e
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Comparison of Alternative Techniques to Achieve Coronary Sinus Cannulation During Biventricular Implantation Procedures

Abstract: Cannulation of CS with the adjunct of an electrophysiology catheter to dedicated delivery systems significantly reduces procedural time, fluoroscopy time and contrast dye volume compared to a conventional strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 8 publications
0
7
0
3
Order By: Relevance
“…Indeed, the use of an IC with a preshaped tip helped the selection of the target vein. We also found that the A is significantly faster than the R system in terms *For this study, 14 there are reported only the patients assigned to the GCA (guiding catheter alone positioning strategy), cannulation strategy. of the median time for LV lead positioning.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Indeed, the use of an IC with a preshaped tip helped the selection of the target vein. We also found that the A is significantly faster than the R system in terms *For this study, 14 there are reported only the patients assigned to the GCA (guiding catheter alone positioning strategy), cannulation strategy. of the median time for LV lead positioning.…”
Section: Discussionmentioning
confidence: 92%
“… *For this study, 14 there are reported only the patients assigned to the GCA (guiding catheter alone positioning strategy), cannulation strategy. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Different maneuvers for CS cannulation, such as preshaped guiding sheaths, 5,6 using a steerable electrophysiological catheter as a guide, 5,7 and over‐the‐wire pacing lead systems, 8 have been recommended in the past. Intracardiac echocardiography 9 and transesophageal echocardiography 10 have also been suggested for assisting CS catheterization in difficult cases.…”
Section: Discussionmentioning
confidence: 99%